Functional Outcome of Total Knee Replacement in Patients with Osteoarthritis Attending Bolan Medical Complex Hospital Quetta - Khawand Bakhsh, M Aslam Mengal, Muhammad Tariq Hasani (Pakistan Journal of Medical & Health Sciences, 2024)
Introduction: Total Knee Arthroplasty (TKA) is an efficient therapeutic option for symptomatic osteoarthritis of the knee that has not improved with conservative treatments. Research has yet to uncover a potentially effective alternative for cartilage regeneration in patients experiencing end-stage degenerative changes that diminish the articular cartilage in various parts of the knee.1 This study is designed to corroborate the outcomes of previous research, and therefore, the same treatment modality will be applied in future cases of patients with osteoarthritis. Objective: To determine the functional outcome of total knee replacement in patients with osteoarthritis presenting at Bolan Medical Complex Hospital Quetta. Study Setting: This descriptive study was conducted at department of Orthopedic Sugary, Bolan Medical Complex Hospital Quetta from 10 March, 2022 to 10 June 2023 Methodology: This study was conducted on seventy one patients of both genders male and female having age between 40 to 65 years diagnosed with osteoarthritis with duration of OA one or more years. The functional outcome of Total Knee Replacement was determined. Results: This study was conducted on 71 patients diagnosed with osteoarthritis. The mean age of the patients was 52.10±7.33 years. According to the functional outcome 18 (25.4%) patients had excellent outcome, 46 (64.8%) had good, 4 (5.6%) had fair and 3 (4.2%) had poor functional outcome. Conclusion: From our study we conclude that the functional outcome of Total Knee Replacement in patients with osteoarthritis was excellent in 25.4%), good in 64.8%), fair in 5.6% and poor in 4.2% patients. Keywords: Osteoarthritis, Total Knee Replacement, Functional outcome, Arthritis